MEDIATION ANALYSIS OF WORK MOTIVATION ON WORKLOAD ON EMPLOYEE PERFORMANCE - Maria Rabiatul Hariroh, Fiqih; Erin Soleha; Muhammad Kosim (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
Research The purpose of this study is to empirically examine work motivation mediating workload on employee performance. The data used in this study used primary data derived from questionnaires and then processed and analyzed and then presented in the form of tables and narratives. The sample used is 300 respondents taken from the population of PT. Amaan Indonesia Prosperous uses the Slovin formula. The sampling technique used is non-probability sampling. In this study, the data analysis technique used is path analysis. The results of the study state that workload has a positive influence on employee performance, work motivation has a positive influence on employee performance, workload has a positive influence on employee performance and motivation variable has a positive influence as a variable that mediates workload on employee performance.